From Pin to Pole: Building an Empire in Daniel Defoe’s Robinson Crusoe - Joshi, Bhupraj (Exploration अन्वेषण, 2026)
Daniel Defoe’s Robinson Crusoe (1719) has long been considered one of the earliest works in the literary canon and one of the foundational novels in English. Yet beneath its narrative of survival and resourcefulness is an attitude of colonialism which reflects the values of the British Empire-building project of the eighteenth century. This essay examines how the story presents issues of hierarchy, binary perception, and the colonial context and psyche of the protagonist through a postcolonial lens, using the theories of Edward Said, Homi K. Bhabha, Gayatri Chakravorty Spivak, and Frantz Fanon, and thus recalls the subsequently developed British Empire. The powerfully negative treatment of the Aboriginal subject, the concern for the superiority of European culture, and Crusoe’s treatment of Friday are discussed as the beginnings of colonial agency-coloniser dynamics. In employing the qualitative method, the analysis focuses on the viewpoints offered by “Orientalism,” “mimicry,” and “the subaltern” in explicating Defoe’s narrative techniques. Robinson Crusoe enjoys personal liberties, but the study reveals the exploitative and domineering qualities of the coloniser. This twofold perception indicates that the work has the potential to act both as a vehicle for colonial myths and as a demonstration of human fortitude. Central to the concluding thoughts of the article is the appropriateness of a postcolonial viewpoint in contemplating the European imperial legacy as well as its critical-literary context.